Gray Matter Deficits and Dysfunction in the Insula Among Individuals With Intermittent Explosive Disorder - Seok, Ji-Woo; Cheong, Chaejoon (Frontiers in Psychiatry, 2020)
Although neuroimaging studies on the characteristics of intermittent explosive disorder (IED) have been accumulating, limited studies exist on the brain structure alterations and focal dysfunction in individuals with IED. This study aimed to identify gray matter deficits and functional alterations in individuals with IED using voxel-based morphometry (VBM) and functional magnetic resonance imaging (fMRI) analyses. Fifteen men with IED and 15 age- and sex-matched healthy controls participated in this study. Gray matter volume and brain activation while viewing the anger-inducing films were measured using 7T MRI. VBM results indicated that individuals with IED had significantly reduced gray matter volume in the insula, amygdala, and orbitofrontal area relative to controls. Gray matter volume in the left insula was negatively correlated with composite aggression scores. fMRI results demonstrated that relative to healthy controls, individuals with IED showed greater activation in the insula, putamen, anterior cingulate cortex, and amygdala during anger processing. Left insula activity was positively correlated with composite aggression scores. Collectively, these findings suggest that structural and functional alterations in the left insula are linked to IED, thereby providing insight into the neural mechanisms underlying IED.